Panorama Francophone 2 Livre du Professeur - Irene Hawkes (Cambridge, United Kingdom Cambridge University Press, 2015)
This teacher's pack accompanies the Panorama francophone 2 student's book and is designed to support teachers in preparing their students for the ab initio French course for the International Baccalaureate Language B programme. The pack contains a teacher's book with answers to all the questions, pedagogical aims of each exercise, advice on lesson structure, examiner's tips, and a chapter on language games. Additional worksheets with extra examination practice, and a student glossary in French, Spanish and English are also provided in the pack (in the CD-ROM).
Keywords: Franch